Daoism and Environmental Philosophy: Nourishing Life: Eric Nelson - Lin, Dongmei; Wang, Jun; Yan, Shengdong (Journal of Dharma, 2021)
Daoism is a religion and a philosophy from ancient China that has influenced folk and national belief. Daoism and Environmental Philosophy: Nourishing Life probes deep into the ethics and philosophy of nature in the Daodejing, the Zhuangzi, and similar texts to illuminate their importance in our current environmental and ecological crises. This book review provides insights for cultivating a more expansive ecological ethos, environmental culture of nature, and political ecology from the view of Daoism.